The Role of Qris as a Digital Payment Revolution to Develop Business in Sendang Asih Beach, Sendangsicat Village, Rowosari District, Kendal Regency - Zulfa Dwi A; Fadilla Qurrata A; Noor Mohammad Rozi; Maryatul Kibtiyah (Universitas Kristen Indonesia Toraja, 2024)
The majority of residents in Sendangsikucing Village are fishermen and some people choose to look for marine products to meet their daily needs, because a fisherman's salary is not commensurate with their needs. Several MSMEs in Sendangsikucing village were important targets in the research. Limited product marketing is an obstacle in increasing sales turnover which is still done manually. The specific aim of implementing the Community Service Program in Sendangsikucing Village, Rowosari District, is to assist the village government in reviving the community economy among MSMEs. Based on payment techniques that still use the manual method, QRIS is the national QR code standard as a code payment medium, where the physical to digital payment method is more efficient. So, it is hoped that this service will be able to help provide positive energy to the community in the transformation towards a cashless society and the results of this activity will be directly put into practice by MSMEs on Sendang Asih beach using the QRIS application for payment transactions. In addition, this research can be used as a valuable reference source for banks or non-bank institutions to develop appropriate strategies to attract MSMEs to use QRIS.